DEVELOPMENT OF LECTORA INSPIRE ASSISTED LEARNING MEDIA TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS - Hesty Parbuntari; Vini Wela Septiana; Debi Anggaraini; Mahmud (Auladuna: Jurnal Pendidikan Dasar Islam, 2024)
Abstract Researchers are concerned about the low level of critical thinking of students in Indonesia and its impact on current generations. Solve this issue, there is a need to develop innovative and interactive learning media using lectora inspire in order to meet the demands of 21st-century learning. This research used the 4D development model (Define, Design, Develop, and Dissemination) and involved grade V elementary school students in West Sumatera province. The developed learning media was assessed for feasibility through tests on media, content, language, and practicality. The results indicated that the interactive learning media assisted by lectora inspire effectively enhanced the critical thinking skills of elementary school students. Experts deemed the media feasible in terms of content, language, and usability. The implementation of lectora inspire-based learning media is seen as a creative and reflective solution to tackle the challenges of the 21st century.